О камне энеолитического могильника Кошары I в бассейне р.Тилигул - Петрунь, В.Ф. (Материалы по археологии Северного Причерноморья, 2019)
The article of V.F. Petrun deals with a petrographic analysis of the collection of stone artifacts from the Eneolithic cemetery Koshary I located in the basin of Tiligul river. The collection was provided for study by Vladislav G. Petrenko. For the analysis of the archaeological materials from Koshary I Victor F. Petrun applied the immersion method (with a polarizing microscope). The article was written by Victor F. Petrun in 2003 and is published for the first time.